Metacercariae of heterodiplostomum lanceolatum (trematoda: Proterodiplostomidae) found in leptodactylus podicipinus (anura: Leptodactylidae) from brazil: A morphological, molecular and ecological study - Queiroz, M. S. [UNESP]; López-Hernández, D.; Locke, S. A.; Pinto, H. A.; Anjos, L. A. [UNESP] (Cambridge University Press (CUP), 2019)
The trematodes from South American reptiles are poorly known, with only one life cycle completely characterized. We used molecular and morphological methods to characterize diplostomoid metacercariae found in 29 of 86 pointedbelly frogs, Leptodactylus podicipinus (Cope, 1862) collected in a marsh pond in Selvíria, in the central-west region of Brazil. The metacercariae were identified as Heterodiplostomum lanceolatum Dubois, 1936 (Proterodiplostomidae), a rarely reported species that matures in snakes. In phylogenetic analysis of partial sequences from 28S rDNA, H. lanceolatum fell within a polytomy with the proterodiplostomid Crocodilicola pseudostoma (molecular divergence of 4.1%) and other members of the superfamily Diplostomoidea. Our collections provide insights into the ecology of this parasite, in that infected frogs were smaller than uninfected frogs, and metacercariae were more numerous in the abdominal cavity and hindlimb muscles than in abdominal muscles, which suggests directions for future research on the transmission and pathology of this proterodiplostomid.
Keywords: Anurans; Life cycle; Metacercariae; Parasites; Proterodiplostomidae; Trematoda